Organizational Amnesia: the Barrier of Value Creation and Organizational Performance in Small and Medium Sized Enterprise - Andi Muhammad Sadat; Mei-Lan Lin (Journal of Business and Behavioural Entrepreneurship, 2018)
Small and medium-sized enterprises (SMEs) in Indonesia has an essential role in economic. Their existence appeared significant when the economy crisis in Asia 1997 and the world economic crisis in 2008. Therefore the existence of SMEs for business and society are imperative, so their sustainability should be maintained through value creation and performance. However, unlike the large companies that typically have resources to maintain information and their knowledge extensively, SME fall into lack of resources that driving them on amnesia consistently (S J Hall & De Raffaele, 2013) and it predispose the ability to create value and company's performance. This paper aims to describe the existence of organizational amnesia (OA) as the failure of organizations to learn reliably at the organizational level (Kransdorff, 1998). This phenomenon is proposed affect SMEs creating value and organizational performance. Some conclusion and future research has been recommended.